Proceso de selección de personal y desempeño laboral de los colaboradores de la Corte Superior de Justicia de Loreto 2022 - Tuesta Rivera, Carlos Enrique (2024)
The objective was to determine the relationship between the selection process and job performance of the Superior Court of Justice of Loreto 2023. The approach was quantitative, applied type, non-experimental design, simple correlational; The sample is made up of 100 collaborators belonging to the Superior Court of Justice of Loreto. 2022; A questionnaire with content validity and Cronbach's Alpha of 0.922 is used. The SPSS V25 statistical program is used to process the data. It was found that the level of evaluation between personnel selection and job performance presents a high level with 76.1% in the Superior Court of Justice of Loreto. It is concluded that there is a significant relationship between personnel selection and job performance in the Superior Court of Justice of Loreto 2022; given the value achieved by the Spearman Compensation Coefficient of 0.781, which indicates high positive compensation, with a level of significance (p<0.05). The selection of personnel and labor performance of the Superior Court of Justice is one of the greatest strengths for the judicial institution, they make up the main elements to achieve the best judicial quality.